Allochrony as a potential driver for reproductive isolation in adaptive radiations of European whitefish ecomorphs - Bitz-Thorsen, Julie; Häkli, Katja; Bhat, Shripathi; Præbel, Kim (Ecology of Freshwater Fish, 2019)
Source at https://doi.org/10.1111/eff.12486 . In northern Fennoscandian lakes, monophylogenetic lineages of postglacial fishes are radiating into several adaptive forms, but the speciation process is still at an incipient stage. The speciation process has received increased attention over the years, but the underlying mechanisms and drivers are still debated and poorly understood. European whitefish ( Coregonus lavaretus [L.]) is the most abundant fish species in these lakes and has evolved into several ecomorphs adapted to different trophic niches and habitats. Genetic divergence has been observed among these ecomorphs, but the mechanism(s) responsible for the ongoing build‐up of reproductive isolation has still to be revealed. As these systems are young in evolutionary time (<10 kyr), prezygotic and postzygotic extrinsic isolation mechanisms are thought to be more likely to contribute to the reproductive isolation than intrinsic isolation mechanisms. We determined the gonadosomatic index (GSI) of three ecomorphs in two replicated lake systems and used GSI as a proxy to investigate the prezygotic isolation mechanism, allochrony, as a driving factor of divergence in this adaptive radiation of whitefish. We found that the three ecomorphs differed in GSI values within and between lakes, suggesting different spawning times of the ecomorphs. We also show that males of one ecomorph had equal onset of maturity as another ecomorph, giving novel insights into the ongoing gene flow observed between ecomorphs. The result supports allochrony as a driver for the divergence process of whitefish ecomorphs, but more evidence is still needed to rule out that the three ecomorphs make use of different spawning grounds.